Assessment of Ecotourism Potential of Mangrove Park Pekalongan Central Java and its Development Strategy - Sodikin Sodikin; Nurismawati Nurismawati; Teuku Rusman Nulhakim; Siti Umamah Naili Muna; Rahmat Hidayat (Universitas Lambung Mangkurat, 2023)
The purpose of this study was to analyze the feasibility of mangrove forests in the Pekalongan Mangrove Park Ecotourism Area in Pekalongan Regency, North Pekalongan City, Central Java as a mangrove ecotourism area and determine a development strategy. This research method used quantitative and qualitative approaches, primary and secondary data obtained from the results of observations, interviews and observations were used as data. The IKW formulation is used as a data analysis technique, and the SWOTL technique is used in the development strategy analysis. The results of the study show that the Pekalongan Mangrove Ecotourism Park which consists of various flora and fauna as well as natural scenery is the main attraction for ecotourism development in Pekalongan City. Based on the results of the suitability analysis, the Pekalongan Mangrove Ecotourism Park has proven to be one of the areas suitable for ecotourism. This is indicated by a swamp suitability index of 68 percent. Alternative Ecotourism Development Strategy SO Mangrove Park Pekalongan will develop all existing groups as an alternative eco-oriented community tourism in Pekalongan City. In the WO Strategy of the Pekalongan City DPRD, provisions are made to maintain and improve the mangrove swamp infrastructure for the Mangrove Ecotourism Area in Pekalongan Park.